Technical and economic evaluation of the utilisation of solar energy at South Africa's Sanae IV Base in Antarctica - Olivier, Jurgen Richter (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2005.